Effects of post-fermentation on the flavor compounds formation in red sour soup - Zhou, Xiaojie; Zhou, Wenhua; He, Xiaojie; Deng, Yaxin; Li, Liangyi; Li, Ming; Feng, Xuzhong; Zhang, Lin; Zhao, Liangzhong (Frontiers in Nutrition, 2022)
Red Sour Soup (RSS) is a traditional fermented food in China. After 2 rounds of fermentation, sour soup has a mellow flavor. However, the mechanism of microbial composition and flavor formation in RSS during post-fermentation is unclear. This study investigated the bacteria composition of RSS during the post-fermentation stage (0 180 days) via using high-throughput sequencing. The results shows that lactic acid bacteria (LAB) were the dominant bacteria in the post-fermentation process, and their abundance gradually increased with fermentation time. Additionally, gas chromatography-mass spectrometry was performed to detect volatile flavour compounds in the post-fermentation process. A total of 77 volatile flavour compounds were identified, including 24 esters, 14 terpenes, 9 aromatic hydrocarbons, 9 alkanes, 6 heterocyclic compounds, 3 alcohols, 3 acids, 3 ketones, 2 phenols, 2 aldehydes, 1 amine, and 1 other. Esters and aromatic hydrocarbons were the main volatile compounds in RSS during the post-fermentation process. Furtherly, there were 67 significant correlations, including 48 pairs of positive correlations and 19 pairs of negative correlations through using orthogonal partial least squares screening and correlation analysis. Among them, Acetobacter spp., Clostridium spp. and Sporolactobacillus spp. showed more than 10 pairs of significant correlations and were considered as the most important bacterial genera in post-fermentation. In addition, volatile substances become abundant with longer fermentation time, LAB are excessive when it is more than 120 days, but causing a drastic reduction of major volatile esters.Thus, the post-fermentation time should be controlled within 120 days, which could keep the highest concentrations of volatile esters in RSS. Overall, these findings provide theoretical basis for determing an optimal duration of post-fermentation and identifying important bacteria for manufacturing high-quality starter to shorten the time during RSS post-fermentation process.